812 views

Which one is the correct translation of the following statement into mathematical logic?

“None of my friends are perfect.”

1. $\neg\:\exists\:x(p(x)\land q(x))$
2. $\exists\:x(\neg\:p(x)\land q(x))$
3. $\exists\:x(\neg\:p(x)\land\neg\:q(x))$
4. $\exists\:x(p(x)\land\neg\:q(x))$

statement.
Sorry, updated now
None of my friends are perfect == Not ( one of my friend is perfect) = Not ( ∃x(p(x)∧q(x)) ) = ¬ (∃x(p(x)∧¬q(x)))

Read it as “All of my friends are not perfect”.

For all x, is x is my friend then he/she is not perfect.

Solving implication will give us our result.

check this

let write a logic for "All my friends are perfect"

$\vee x(q(x)\rightarrow p(x))$

take negation of above "none of my friends are perfect"

$\sim(\vee x(q(x)\rightarrow p(x)))$

$\sim\vee x (\sim q(x)\vee p(x))))$

$Ǝx(q(x)\wedge \sim p(x))$

Correct me if I am wrong.

What is p(x) and q(x) here?

“None of my friends are perfect.”

It says that It is a false that i have friend and he is perfect

$\sim \exists x(P(x) \wedge q(x)))$

by

1
1,822 views